Advances in the Pathogenesis of EBV-Associated Diffuse Large B Cell Lymphoma - Chabay, Paola Andrea (2021)
Diffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin’s lymphoma (NHL) in adults. Epstein–Barr virus (EBV) positive DLBCL of the elderly was defined by the World Health Organization (WHO) in 2008, it was restricted only to patients older than 50 years old, and it was attributed to immunesenescence associated with physiological aging. After the description of EBV-associated DLBCL in children and young adults, the WHO redefined the definition, leading to the substitution of the modifier “elderly” with “not otherwise specified” (EBV + DLBCL, NOS) in the updated classification, and it is no more considered provisional. The incidence of EBV + DLBCL, NOS varies around the world, in particular influenced by the percentage of EBV+ cells used as cut-off to define a case as EBV-associated. EBV has effect on the genetic composition of tumor cells, on survival, and at the recruitment of immune cells at the microenvironment. In this review, the role of EBV in the pathogenesis of DLBCL is discussed.